THE EFFECT OF RESTAURANT ATMOSPHERE AND SALES PROMOTION ON REPURCHASE INTENTION MEDIATED BY CUSTOMER SATISFACTION (A STUDY ON HORSE COFFEE & EATERY) - Inggit Nurmarita Dewi; Ni Made Rastini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the Food and Beverage sector have recently experienced rapid development. One of these business phenomena is coffee shops. Thousands of coffee shops in Indonesia are now mushrooming to various regions, requiring business owners to be creative and able to follow developments by creating good marketing strategies that can generate repeat purchase intentions. Strategies that can be developed to generate repeat purchase intentions can be done by improving the restaurant atmosphere and creating attractive sales promotions. In reality, not all cafes have high repeat purchase intentions, including Horse Coffee & Eatery. This study aims to explain the influence of restaurant atmosphere and sales promotions on repeat purchase intentions mediated by customer satisfaction. Data collection was carried out by distributing questionnaires. The sampling technique in this study was purposive sampling. The sample used was 140 consumers who met the criteria. The data analysis technique used Path Analysis. The results of the study indicate that, 1) restaurant atmosphere and sales promotion have a positive and significant effect on repurchase intention, 2) restaurant atmosphere and sales promotion have a positive and significant effect on customer satisfaction, 3) customer satisfaction has a positive and significant effect on repurchase intention, 4) customer satisfaction acts as a partial mediator in the influence of restaurant atmosphere and sales promotion on repurchase intention. Based on these results, it is recommended that Horse Coffee & Eatery be able to maintain cleanliness, provide economical packages, and better service to attract consumer repurchase intention.